2019
DOI: 10.33494/nzjfs492019x26x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fallen logs from high-resolution UAV images

Abstract: Background: High-resolution images from unmanned aerial vehicles (UAVs) can be used to describe the state of forests at regular time periods in a cost-effective manner. The purpose of this study was to assess the performance of a line template matching algorithm, the Hough transformation, for detecting fallen logs from UAV-based high-resolution RGB images. The suggested methodology does not aim to replace any known aerial method for log detection, rather it is more oriented to the detection of fallen logs in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Other studies mapping logs on aerial images were able to detect logs with comparable accuracy, such as Baumann et al [9] with about 68% and 95%, Duan et al [16] with 75.7% and 92.5%, Rüetschi et al [11] with 88% and 85%, and Panagiotidis et al [17] with 84.6% and 94.9% completeness and correctness, respectively. However, the accuracies in the present study reflect more challenging conditions involving CWD in diverse settings-natural and disturbed forest-at varying stages of decomposition and over a large application area.…”
Section: General Accuracy and Transferabilitymentioning
confidence: 78%
“…Other studies mapping logs on aerial images were able to detect logs with comparable accuracy, such as Baumann et al [9] with about 68% and 95%, Duan et al [16] with 75.7% and 92.5%, Rüetschi et al [11] with 88% and 85%, and Panagiotidis et al [17] with 84.6% and 94.9% completeness and correctness, respectively. However, the accuracies in the present study reflect more challenging conditions involving CWD in diverse settings-natural and disturbed forest-at varying stages of decomposition and over a large application area.…”
Section: General Accuracy and Transferabilitymentioning
confidence: 78%
“…The overall accuracy increased steadily with the increase in the stump diameter. In the same vein as Puliti et al (2018), Panagiotidis et al (2019) assessed the detection of fallen logs from RPAS images of very high resolution. Their importance occurs mainly in areas that are difficult to access and for a quick assessment of damages such as those caused by wind.…”
Section: Postharvest Assessmentsmentioning
confidence: 99%
“…Challenges in CWD field sampling techniques (Ståhl et al 2001;Woldendorp et al 2004), as well as the relevance of dead wood in a host of forest ecosystem functions (Woodall et al 2019), have sparked an interest in applying remotely sensed data for this purpose. For example, CWD objects have recently been detected with encouraging results using LiDAR point clouds (Polewski et al 2015;Joyce et al 2019), aerial photography by means of Unmanned Aerial Vehicles (UAV) (Inoue et al 2014;Duan et al 2017;Panagiotidis et al 2019), or using LiDAR combined with multispectral aerial photography (Richardon and Moskal 2016;Stereńczak et al 2017;Lopes Queiroz et al 2019). Alternatively, models can be established leveraging spectral and structural relationships between plot-level observations of CWD volume and LiDAR or winter Landsat scenes (Sumnall et al 2016;Wolter et al 2017).…”
Section: Remote Sensing Of Coarse Woody Debrismentioning
confidence: 99%
“…Despite the use of VHR imagery and high-density point clouds, studies have reported challenges in the detection of smaller CWD objects due to high densities of small overlapping or parallel objects, occlusions, and shadowing, with reported plot-level CWD object detection rates of 23%-25% (Inoue et al 2014; Joyce et al 2019) and rates of small logs (e.g., <5 m, 20 cm DBH) as low as 5% (Inoue et al 2014; Panagiotidis et al 2019). Subarctic montane woodlands are considerably less productive than southern boreal or temperate forests whereby limited size of CWD pieces can be expected.…”
Section: Remote Sensing Of Coarse Woody Debrismentioning
confidence: 99%